2012
DOI: 10.4018/jictrda.2012010102
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Market of Sub-Saharan Africa and Technology Adoption

Abstract: In the United States, Organization for Economic Co-operation and Development (OECD) countries and several emerging economies in Asia, mobile technologies have become ubiquitous and core to everyday lives. The same cannot be said for many countries in Sub Saharan Africa (SSA). The availability, affordability and use of information and communication technology (ICT) continue to pose a major challenge to the progress of this important emerging economy and their participation in a networked and “flat world.” Write… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The improved technological integration has also led to an increased usage of mobile devices, providing an opportunity for distance education. Technology companies have set up their marketing shops in various African countries, including South Africa, Nigeria, and Kenya enhancing the demand for distance education, especially for postgraduate students already in professional fields [31]. Technological devices have made it easier to access digital and social media, such as Youtube and LinkedIn, which are all critical in networking and learning new information.…”
Section: Conditions For Distance Educationmentioning
confidence: 99%
“…The improved technological integration has also led to an increased usage of mobile devices, providing an opportunity for distance education. Technology companies have set up their marketing shops in various African countries, including South Africa, Nigeria, and Kenya enhancing the demand for distance education, especially for postgraduate students already in professional fields [31]. Technological devices have made it easier to access digital and social media, such as Youtube and LinkedIn, which are all critical in networking and learning new information.…”
Section: Conditions For Distance Educationmentioning
confidence: 99%
“…Such that developing countries find it challenging to even transfer money (Razzaque et al 2019 ; Collins et al 2009 ). In such countries when the financial sector introduces e-payment and e-banking systems, such regions also experience a commendable accomplishment (Etim 2012 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, it is reported that the introduction of mobile phones services in agricultural sector in Pakistan, India, Brazil, and the United States of America has enabled farmers and other actors in the different value chains to receive high amount and quality of the agricultural extension service. In addition, the speed of services delivery has been improved significantly as a result of mobile phone intervention (Thomson, 2006;Buys et al, 2009;Aker & Mbiti, 2010;Goggin, 2012;Acker, 2011;Etim, 2012a;Etim, 2012b;Etim, 2013c).…”
Section: Background Informationmentioning
confidence: 99%